2017
DOI: 10.1097/ijg.0000000000000730
|View full text |Cite
|
Sign up to set email alerts
|

Optic Nerve Head Drusen: Imaging Using Optical Coherence Tomography Angiography

Abstract: This is the first report in which peripapillary vessel density is analyzed using OCTA technology for this entity. OCTA could confirm the diagnosis and has the potential to assist with the diagnosis and evaluation of progression of ONHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…A focal decrease in vessel density within the location of optic nerve head drusen in pseudopapilledema has been shown in one case report,21 and overall decreased vessel density in a cohort of 13 patients with optic disc drusen was recently described as well 22. Small, elevated, and crowded optic discs in pseudopapilledema might compress peripapillary nerve fiber layer, which then impair retinal blood flow to the peripapillary retina in pseudopapilledema including optic disc drusen 21. A similar peripapillary ischemic feature might happen in severe papilledema eyes, accounting for our finding no differences in any capillary values when we compared eyes with grade 3 papilledema with pseudopapilledema eyes.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…A focal decrease in vessel density within the location of optic nerve head drusen in pseudopapilledema has been shown in one case report,21 and overall decreased vessel density in a cohort of 13 patients with optic disc drusen was recently described as well 22. Small, elevated, and crowded optic discs in pseudopapilledema might compress peripapillary nerve fiber layer, which then impair retinal blood flow to the peripapillary retina in pseudopapilledema including optic disc drusen 21. A similar peripapillary ischemic feature might happen in severe papilledema eyes, accounting for our finding no differences in any capillary values when we compared eyes with grade 3 papilledema with pseudopapilledema eyes.…”
Section: Discussionmentioning
confidence: 85%
“…Nasal PCD of <22.6% had 69% specificity and 63% sensitivity and the whole image capillary of irVD image of <22.8% had 74% specificity and 60% sensitivity for differentiating pseudopapilledema from papilledema. A focal decrease in vessel density within the location of optic nerve head drusen in pseudopapilledema has been shown in one case report,21 and overall decreased vessel density in a cohort of 13 patients with optic disc drusen was recently described as well 22. Small, elevated, and crowded optic discs in pseudopapilledema might compress peripapillary nerve fiber layer, which then impair retinal blood flow to the peripapillary retina in pseudopapilledema including optic disc drusen 21.…”
Section: Discussionmentioning
confidence: 91%
“…More recently, OCT angiography (OCTA) has been used to detect microvascular changes in the peripapillary and macular areas in different optic neuropathies (19) including ODD (20). Previous studies found that eyes with ODD had focal microvascular attenuation corresponding to the drusen (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have investigated the role of cerebrospinal fluid pressure on optic nerve head biomechanics, demonstrating that elevating cerebrospinal fluid pressure results in increased deformation of the lamina cribrosa and retrolaminar optic nerve, and that this deformation resolves within weeks following an intervention to lower cerebrospinal fluid pressure (14,15) . (12) argued that the study group in all the studies in favor of using OCT as a tool to differentiate between disc edema and pseudopapilledema had subjects with variable causes of disc swelling in the group with disc edema and could not be used to represent papilledema (16) . Though previous studies have found total retinal thickness to perform better than retinal nerve fiber layer thickness (17,18) .…”
Section: Discussionmentioning
confidence: 99%